La lúdica como estrategia metodológica, en el desarrollo de la lecto-escritura de los niños de tercer año, de la escuela de Educación Básica E.B. Filomena Mora de Carrión, cantón Loja, durante el primer quimestre del periodo académico 2018- 2019. Lineamientos Alternativos AUTOR Wilman Santiago Gonzaga Sarango DIRECTOR DE TESIS Dr. Israel Fernando Ramón Salcedo Mg. Sc LOJA-ECUADOR 2019 Tesis previa a la obtención del Grado de Licenciado - Gonzaga Sarango, Wilman Santiago (2019)
The thesis "The playful as a methodological strategy, in the development of reading-writing of children of the third year, of the School of Basic Education E.B. Filomena Mora de Carrión, Loja canton, during the first semester of the academic period 2018-2019. Alternative Guidelines "has as its general objective: To analyze the playful as a methodological strategy and its application in the development of reading and writing, of third grade children year, of the Basic Education School EB Filomena Mora de Carrión, Loja canton, during the first quarter of the academic period 2018-2019; the approach used was mixed and of qualitative-quantitative design; the methods applied were scientific, descriptive, analytic-synthetic, inductive, deductive, and statistical; the techniques, observation, survey, interview; instruments such as questionnaire, question guide and checklist; they were executed based on the theoretical foundation, diagnosis and design of the alternative guidelines. Among the main results obtained, it can be mentioned that the play strategies used in the classroom are not adequate for learning to read, which generates demotivation and boredom in the students; The population investigated was 25 students and a teacher. It is concluded that the use of ludic methodological strategies are of vital importance for students to acquire reading and writing skills in an appropriate manner